Renal failure in otherwise uncomplicated acute viral hepatitis. - Wilkinson, S P (1978)
Twelve patients with otherwise uncomplicated acute viral hepatitis (two were HBsAg-positive) developed renal failure. Apart from dehydration due to repeated vomiting in one patient, no factor responsible for precipitating renal failure could be identified. The clinical course was characterised by renal failure with plasma urea concentrations reaching maximum values of 26-69 mmol/l (175-416 mg/100 ml). Ten patients needed dialysis for up to two weeks. Seven patients recovered completely, while the other five died from sepsis. The types of renal failure were similar to those described in fulminant hepatic failure and cirrhosis--namely, functional renal failure in five patients and acute tubular necrosis in seven. Two of the patients with functional renal failure later developed tubular necrosis. The mechanism responsible for renal failure in acute viral hepatitis is uncertain, though endotoxaemia may contribute.